INCREASED ADHERENCE TO WARFARIN TREATMENT WITH TRAINING PROGRAMS IN PATIENTS WITH ATRIAL FIBRILLATION - E. D. Djishambaev; S. I. Khakimova; A. M. Shatenova; E. N. Murzalieva; D. A. Usupbaeva (Евразийский Кардиологический Журнал, 2020)
Purpose of the study: to assess the role of educational programs on anticoagulant therapy in patients with atrial fibrillation in increasing adherence to warfarin treatment.Material and methods: the study included patients with atrial fibrillation, divided into two groups: the main group (n=125) - patients who completed the training program, and the control group (n=216), randomized for routine care, without training sessions. Comparison of the groups were comparable in sex (55.8% of men and 44.2% of women – in main group and 62.4% of men (p<0.3) and 37.6% (p<0.3) - in the control group) and age (64.0±10.4 and 62.0±11.4 years, respectively, p<0.1). Stroke risk was assessed using the CHA2DS2-VASc scale.Results: the average CHA2DS2-VASc score in the main group was 2.4±1.2 for men and 3.4±1.2 for women. In the control group, this indicator was 2.5±1.3 for men, and 3.5±1.2 for women. Although the number of patients who regularly took warfarin in the main and control groups did not differ significantly (61.4% and 54.9%, respectively, p=0.2), the number of patients who took oral anticoagulants (warfarin + rivaroxaban) in the main group was 85.5%, which turned out to be significantly higher than the data of the control group - 61.5% (p=0.002). Among the patients who underwent training, there were significantly more people who regularly monitor INR, comparing to control group (80.4% versus 44.0%, p=0.005). At the same time, the number of patients who achieved the target INR in the main group was also significantly higher in comparison with the control group (66.7% versus 36.0%, p=0.04).Conclusion: conducting a course of educational programs among patients with atrial fibrillation increases adherence to the prescribed treatment with warfarin. This is manifested by increased number of patients, who regularly take the drug and monitor INR, as well as a significant increased number of patients who have reached the target INR levels.